A high thermal conductivity adaptive composite film and preparation method thereof
By doping ZnO-based inorganic fillers and carbon nanotubes into the insulating layer of IGBT devices, a conductive and thermal network is formed, which solves the problem of degradation of insulation performance of existing insulating layer materials at high temperatures, and achieves high thermal conductivity and high stability The composite film improves the heat dissipation performance of IGBT devices.
Patent Information
- Application Number
- CN202311233700.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-09-22
AI Technical Summary
The insulation layer material of existing IGBT devices, silicon gel, reduces the insulation performance when the temperature rises, resulting in local discharge and breakdown, which cannot meet the heat dissipation needs in high temperature environments.
A highly thermally conductive adaptive composite film is used as the insulating layer, and the conductive network and thermal network are formed by doping ZnO-based inorganic fillers and carbon nanotubes into the rubber matrix film to improve the heat dissipation performance.
It improves the thermal conductivity and electrical conductivity of the composite film, enhances the heat dissipation ability of the IGBT device, avoids local discharge and breakdown, and is suitable for high-temperature environments.
Smart Images

Figure CN117487354B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of membrane technology, and in particular relates to a high-thermal-conductive adaptive composite membrane and a preparation method thereof. Background Art
[0002] IGBT is a semiconductor device, which belongs to the voltage control device. It is used to adjust the voltage, current, frequency, phase, etc. in the circuit. It is mainly used in electric / hybrid vehicles, rail transit, variable frequency home appliances, power engineering, renewable energy and smart grid. The packaging structure of IGBT devices mainly includes substrates, insulating layers, etc. The substrate is used to support the IGBT chip, and the insulating layer is used for insulation. The normal working temperature range of IGBT devices is -40℃~150℃. Therefore, in order to maintain the normal operation of the IGBT chip, heat dissipation is required. The improvement of the performance of IGBT devices depends largely on the improvement of heat dissipation performance. At present, the insulating layer is mainly silicone gel, etc. Since the insulating performance of silicone gel will decrease with the increase of temperature, in the long run, the withstand field strength of silicone gel will be lower than the maximum field strength of the device, resulting in partial discharge and even breakdown. Therefore, how to provide a composite film with excellent heat dissipation performance as an insulating layer is a technical problem that needs to be solved in this field. Summary of the invention
[0003] The present invention provides a highly thermally conductive adaptive composite film, which effectively improves the heat dissipation performance of the composite film by limiting the components of the composite film.
[0004] In a first aspect of the present invention, there is provided a highly thermally conductive adaptive composite membrane, comprising a rubber matrix membrane and ZnO-based inorganic fillers and carbon nanotubes doped in the rubber matrix membrane;
[0005] The ZnO-based inorganic filler and the carbon nanotubes are independently doped inside and / or on the surface of the rubber matrix film.
[0006] The composite film as described above, wherein the composite film comprises the following components in parts by mass: 20-30 parts of rubber matrix, 60-80 parts of ZnO-based inorganic filler, 0.1-10 parts of carbon nanotubes, and 0.5-1 part of vulcanizing agent.
[0007] The composite film as described above, wherein the particle size of the ZnO-based inorganic filler is 10 to 30 μm;
[0008] The carbon nanotube has an inner diameter of 2-5 nm, an outer diameter of less than 8 nm, and a length of 10-30 μm.
[0009] The composite film as described above, wherein the ZnO-based inorganic filler comprises ZnO and a dopant doped in the ZnO;
[0010] Wherein, the dopant includes at least one of Bi2O3, MnO2, Co2O3, Cr2O3, Sb2O3, SiO2, and Al2O3.
[0011] The composite film as described above, wherein the rubber matrix comprises at least one of styrene-butadiene rubber and silicone rubber; and / or,
[0012] The thickness of the composite film is 190-210 μm.
[0013] The composite film as described above, wherein the thermal conductivity of the composite film is 1 to 1.5 W / mK.
[0014] The second aspect of the present invention provides a method for preparing the high thermal conductivity adaptive composite film according to the first aspect, comprising the following steps:
[0015] The rubber matrix, the ZnO-based inorganic filler, the carbon nanotubes and the vulcanizing agent are mixed to obtain a composite material;
[0016] The composite material is subjected to hot pressing treatment and cold pressing treatment in sequence to obtain a composite film.
[0017] The preparation method as described above, wherein the ZnO-based inorganic filler is prepared by a method comprising the following steps: ZnO and a dopant are mixed in proportion, and the mixture is subjected to ball milling and sintering to obtain the ZnO-based inorganic filler; and / or,
[0018] The process of mixing the rubber matrix, the ZnO-based inorganic filler, the carbon nanotubes, and the vulcanizing agent includes:
[0019] The rubber matrix, the ZnO-based inorganic filler and the carbon nanotubes equivalent to 10-20wt% of the total amount of the reaction raw materials are mixed under the first condition to obtain a first mixed system; the remaining rubber matrix, the carbon nanotubes and the ZnO-based inorganic filler are sequentially added to the first mixed system under the first condition to obtain a second mixed system; wherein the temperature under the first condition is 20-40°C and the rotation speed is 5-10r / min;
[0020] After the second mixed system is subjected to a first speed-increasing treatment, a vulcanizing agent is added to the second mixed system under a second condition for reaction; wherein the rate of the first speed-increasing treatment is 5 to 10 r / min, the interval time is 20 to 30 s, the temperature of the second condition is 20 to 40° C., and the rotation speed is 50 to 60 r / min.
[0021] The preparation method as described above, wherein the temperature of the hot pressing treatment is 170-180° C., the pressure is 10-15 MPa, and the time is 5-10 min; and / or,
[0022] The temperature of the cold pressing treatment is 20°~25℃ and the time is 5~10min.
[0023] The preparation method as described above, wherein the ball milling treatment is performed at a temperature of 20° to 40° C. for a time of 8 to 10 h; and / or,
[0024] The sintering temperature is 1200°C to 1300°C, and the sintering time is 4 to 6 hours.
[0025] The implementation of the present invention has at least the following beneficial effects:
[0026] The composite film provided by the present invention is prepared by doping ZnO-based inorganic fillers and carbon nanotubes into a rubber matrix film. Since the carbon nanotubes are semiconductors with relatively high electrical conductivity, the rubber matrix film can have certain electrical conductivity, which will not cause certain influence on the nonlinear electrical conductivity characteristics of the composite film, and is beneficial to improving the thermal conductivity of the composite film. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a SEM image of a cross section of the composite membrane in Example 1 of the present invention;
[0028] Figure 2 is a SEM image of a cross section of the composite membrane in Example 2 of the present invention;
[0029] Figure 3 is a SEM image of a cross section of the composite membrane in Example 3 of the present invention;
[0030] Figure 4 is a SEM image of a cross section of the composite membrane in Example 4 of the present invention;
[0031] Figure 5 is a SEM image of a cross section of the composite membrane in Example 5 of the present invention;
[0032] Figure 6 is a SEM image of a cross section of the composite membrane in Example 6 of the present invention;
[0033] Figure 7 is a SEM image of a cross section of the composite membrane in Example 7 of the present invention;
[0034] Figure 8 is a SEM image of a cross section of the composite membrane in Example 8 of the present invention;
[0035] Fig. 9 is a SEM image of a cross section of the composite membrane in Example 9 of the present invention;
[0036] Fig.10 is a SEM image of a cross section of the composite membrane in Example 10 of the present invention;
[0037] Fig.11is a SEM image of a cross section of the composite membrane in Comparative Example 1 of the present invention;
[0038] Fig.12 is a SEM image of a cross section of the composite membrane in Comparative Example 2 of the present invention;
[0039] Fig.13 is a SEM image of a cross section of the composite membrane in Comparative Example 3 of the present invention;
[0040] Fig.14 is a SEM image of the ZnO-based inorganic filler at a first angle in Example 1 of the present invention;
[0041] Fig.15 is a SEM image of the ZnO-based inorganic filler in Example 1 of the present invention at a second angle;
[0042] Fig.16 is an IU characteristic curve diagram of the composite membranes in Examples 1 to 10 of the present invention and Comparative Examples 1 to 3;
[0043] Fig.17 It is a test diagram of thermal properties of the composite membranes in the embodiments of the present invention and the comparative examples. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] The first aspect of the present invention provides a highly thermally conductive adaptive composite membrane, comprising a rubber matrix membrane and ZnO-based inorganic fillers and carbon nanotubes doped in the rubber matrix membrane; the ZnO-based inorganic fillers and carbon nanotubes are independently doped in the interior and / or surface of the rubber matrix membrane.
[0046] According to the research of the present invention, the application of the above-mentioned composite film in IGBT devices is beneficial to improving the heat dissipation performance. This is because by doping ZnO-based inorganic fillers and carbon nanotubes into the interior and / or surface of the rubber matrix film, the ZnO-based inorganic fillers and carbon nanotubes form an interconnected conductive network and a thermal conductive network in the rubber matrix film, which can not only ensure the nonlinear conductivity characteristics of the composite film, but also help to improve the heat dissipation performance.
[0047] The present invention does not limit the specific mass composition of the composite film, as long as the composite film is formed. For example, in some embodiments, the composite film includes the following components by mass: 20-30 parts of rubber matrix, 60-80 parts of ZnO-based inorganic filler, 0.1-10 parts of carbon nanotubes, and 0.5-1 parts of vulcanizing agent. The role of the vulcanizing agent is to promote film formation and connect the ZnO-based inorganic filler, carbon nanotubes and rubber matrix.
[0048] By limiting the mass fraction of the above components, it is beneficial to take into account both the on-state voltage and mechanical properties of the composite film. When the filling amount of ZnO-based inorganic fillers and carbon nanotubes is low, the contact interface between the particles cannot be stably formed, and it is difficult to obtain a nonlinear conductivity composite film that meets the application requirements; and although a nonlinear conductivity composite film that meets the application requirements can be obtained by increasing the filling amount of fillers, it will inevitably be accompanied by the problem of deterioration of the mechanical properties of the composite film due to high filling.
[0049] The present invention does not limit the diameter of the ZnO-based inorganic filler and the carbon nanotube, as long as the ZnO-based inorganic filler and the carbon nanotube form a connected thermal and electrical conductive network in the rubber matrix. For example, in some embodiments, the particle size of the ZnO-based inorganic filler is 10 to 30 μm; the diameter of the carbon nanotube is an inner diameter of 2 to 5 nm and an outer diameter of <8 nm. The carbon nanotube can be a multi-walled carbon nanotube.
[0050] The present invention does not limit the specific type of ZnO-based inorganic filler, which can be obtained by conventional methods, such as from Xi'an Daoshun Smart Non-metallic Materials. For example, in some embodiments, the ZnO-based inorganic filler includes ZnO and a dopant doped in ZnO; wherein the dopant includes Bi2O3, MnO2, Co2O3, Cr2O3, Sb2O3, SiO2, and Al2O3.
[0051] In the specific implementation process of the present invention, the preparation process of the ZnO-based inorganic filler includes the following steps: ZnO and dopant are placed in a ball mill, and anhydrous ethanol is added for ball milling for 8 hours, and then an organic binder is added to the ball-milled slurry, and the slurry is poured into a spray granulator for spray granulation to obtain spherical particles with a particle size of 10 to 30 μm. Then sintering is performed to obtain the ZnO-based inorganic filler.
[0052] The present invention does not limit the specific type of the rubber matrix, which may be a conventional rubber matrix in the art. For example, in some embodiments, the rubber matrix includes at least one of styrene-butadiene rubber and silicone rubber; and / or the thickness of the composite film is 190 to 210 μm.
[0053] The present invention does not limit the thermal conductivity of the composite film, as long as the composite film includes the above components. For example, in some embodiments, the thermal conductivity of the composite film is 1 to 1.5 W / mK. The thermal conductivity is obtained by testing for 20 seconds at room temperature 25°C and 2W power using a thermal constant analyzer (Hot Disk).
[0054] The second aspect of the present invention provides a method for preparing a highly thermally conductive adaptive composite membrane, comprising the following steps: mixing a rubber matrix, a ZnO-based inorganic filler, carbon nanotubes, and a vulcanizing agent to obtain a composite material; and sequentially performing hot pressing and cold pressing on the composite material to obtain a composite membrane.
[0055] Among them, since the rubber matrix is a thermosetting material, a vulcanizing agent is required in the mixing process.
[0056] In some embodiments, the ZnO-based inorganic filler is prepared by a method comprising the following steps: ZnO and a dopant are mixed in proportion, ball milled, spray dried, and sintered to obtain the ZnO-based inorganic filler, wherein the ball milling temperature is 20 to 40°C for 8 to 10 hours; and / or the sintering temperature is 1200 to 1300°C for 4 to 6 hours.
[0057] The mixing effect can be greatly improved by controlling the process conditions such as the order of adding each component raw material, rotation speed and time during the mixing process.
[0058] In some embodiments, the process of mixing a rubber matrix, a ZnO-based inorganic filler, a carbon nanotube, and a vulcanizing agent includes: mixing a rubber matrix, a ZnO-based inorganic filler, and a carbon nanotube equivalent to 10 to 20 wt% of the total amount of the reaction raw materials under a first condition to obtain a first mixed system; adding the remaining rubber matrix, carbon nanotubes, and ZnO-based inorganic filler to the first mixed system in sequence under the first condition to obtain a second mixed system; wherein the temperature under the first condition is 20 to 40°C and the rotation speed is 5 to 10 r / min; after the second mixed system is subjected to a first speed increase treatment, a vulcanizing agent is added to the second mixed system under a second condition for reaction; wherein the rate of the first speed increase treatment is 5 to 10 r / min, the interval time is 20 to 30s, and the temperature of the second condition is 20 to 40°C and the rotation speed is 50 to 60 r / min.
[0059] The mixing process can be carried out by conventional mixing equipment in the art, such as a torque rheometer internal mixer, which is conducive to controlling the speed and temperature during mixing. The torque rheometer model is RM-200C, manufactured by Harbin Harpu Electric Technology Co., Ltd., with a capacity of 60 mL, a temperature upper limit of 350°C, a rotor speed ratio of 3:2, and a torque measurement range of 0 to 230 Nm.
[0060] Furthermore, the order of addition can be adjusted according to the density of each component raw material to prevent the raw material with high density from gradually sinking. In order to mix more evenly, the principle of adding the lowest density first is followed. For example, when the density of the ZnO-based inorganic filler is greater than the density of the rubber matrix and the density of the carbon nanotubes, the carbon nanotubes, ZnO-based inorganic filler, and rubber matrix are added in this order.
[0061] The present invention does not limit the method of adding the rubber matrix, carbon nanotubes, and ZnO-based inorganic filler. For example, the rubber matrix, carbon nanotubes, and ZnO-based inorganic filler are each evenly divided into 5 portions, and added in the order of rubber matrix, carbon nanotubes, and ZnO-based inorganic filler in 5 times, with the time interval between each cycle of addition being 10 to 20 seconds.
[0062] The added amount of the vulcanizing agent can be 0.5% to 1% of the total amount of the rubber matrix, the carbon nanotubes and the ZnO-based inorganic filler.
[0063] The present invention does not limit the conditions of the hot pressing treatment, as long as the rubber matrix is vulcanized and formed under high temperature and high pressure. For example, in some embodiments, the hot pressing treatment temperature is 170-180°C, the pressure is 10-15 MPa, and the time is 5-10 minutes.
[0064] The present invention does not limit the conditions of the cold pressing treatment. For example, in some embodiments, the temperature of the cold pressing treatment is 20° to 25° C., and the time is 5 to 10 minutes.
[0065] Among them, hot pressing treatment and cold pressing treatment can be operated by a flat hot press, for example: a flat hot press, model YT-LH75A, manufactured by Dongguan Yitong Testing Equipment Technology Co., Ltd., places the composite material between the working plates, sets the time, temperature, and pressure, and vulcanizes the composite material under high temperature and high pressure. The temperature range is 20℃~300℃, the maximum pressure is 15MPa, and the temperature accuracy is ±1℃.
[0066] The present invention is further described below by specific examples and comparative examples. Unless otherwise specified, the reagents, materials and instruments used below are all conventional reagents, conventional materials and conventional instruments, which can be commercially available, and the reagents and materials involved can also be synthesized by conventional synthesis methods.
[0067] The preparation process of the ZnO-based inorganic filler comprises the following steps: 95 mol% ZnO, 1.0 mol% Bi2O3, 0.5 mol% MnO2, 1.0 mol% Co2O3, 0.4 mol% Cr2O3, 1 mol% Sb2O3, 1.0 mol% SiO2 and 0.1 mol% Al2O3 are mixed, put into a ball mill, and then anhydrous ethanol is added for ball milling for 8 hours; then, an organic binder is added to the ball-milled slurry, and the slurry is poured into a spray granulator for spray granulation to produce spherical particles; the spherical particles are put into a calcining furnace, the temperature is increased to 1250°C at a rate of 5.5°C / min, and after sintering for 4.5 hours, the temperature is lowered at a rate of 1.6°C / min to obtain a sintered product; the sintered product is sieved through a standard sieve to obtain a ZnO-based inorganic filler with a particle size of 10 to 20 μm.
[0068] The base is silicone rubber, model NE-5130 / NE-5140 / NE-5150, milky white solid, thermosetting material, density 1.2g / cm 3 , provided by Tianjin Yihuachang New Materials Technology Co., Ltd.
[0069] The curing agent is dipentadienyl vulcanizing agent, 2,5-dimethyl-2,5-dihexane, milky white powder, boiling point 50-52°C, provided by Weihai Guangwei Composite Materials Co., Ltd.
[0070] Multi-walled carbon nanotubes, purity > 95%, inner diameter 2-5 nm, outer diameter < 8 nm, length 10-30 μm, density 2.1 g / mL, provided by Shanghai McLean Biochemical Technology Co., Ltd.
[0071] Example 1
[0072] The weight of each component is calculated according to the torque rheometer capacity × volume ratio × density, where the density of the ZnO-based inorganic filler is 5g / cm 3 The density of multi-walled carbon nanotubes is 0.09 g / cm 3 The density of the rubber matrix is 1.2g / cm 3 , the capacity of the torque rheometer is 60 mL, and the mass of the vulcanizing agent is 0.8% of the total mass of the ZnO-based inorganic filler, multi-walled carbon nanotubes, and rubber matrix;
[0073] First, 0.27g of multi-walled carbon nanotubes was added to the torque rheometer, and then 120g of ZnO-based inorganic filler and 39.6g of rubber matrix were divided into 10 parts and added in sequence at a temperature of 40° and a rotation speed of 5r / min, and then the rotation speed was gradually increased to 60r / min and stirred for 15min, and finally 1.5987g of dipentadienyl vulcanizing agent was added at a rotation speed of 60r / min, and stirred for another 5 minutes to obtain a composite material; wherein, gradually increasing to 60r / min means increasing the rotation speed from 5r / min, the speed increase rate range is 5r / min to 10r / min, and the interval time range is 20s to 30s, until the rotation speed is increased to 60r / min;
[0074] The composite material is weighed according to the volume of the tableting mold × density, wherein the size of the mold is 200 μm × 12 cm × 12 cm, and the density of the composite material is calculated by the density of each component × volume percentage and the sum of the two;
[0075] The weighed composite material is first vulcanized by hot pressing at 170°C and 15 MPa for 5 minutes in a torque rheometer, and then cold pressing at 20°C and 15 MPa for 5 minutes to obtain a composite film.
[0076] Example 2
[0077] The preparation process is basically the same as that in Example 1, except that “120 g ZnO-based inorganic filler, 0.27 g multi-walled carbon nanotubes, 39.6 g rubber matrix, 1.5987 g vulcanizing agent” is replaced by “105 g ZnO-based inorganic filler, 0.27 g multi-walled carbon nanotubes, 43.2 g rubber matrix, 1.4847 g vulcanizing agent”, and other conditions remain unchanged.
[0078] Example 3
[0079] The preparation process is basically the same as that in Example 1, except that “120 g ZnO-based inorganic filler, 0.27 g multi-walled carbon nanotubes, 39.6 g rubber matrix, 1.5987 g vulcanizing agent” is replaced by “114 g ZnO-based inorganic filler, 0.27 g multi-walled carbon nanotubes, 41.04 g rubber matrix, 1.5531 g vulcanizing agent”, and other conditions remain unchanged.
[0080] Example 4
[0081] The preparation process is basically the same as that in Example 1, except that “120 g ZnO-based inorganic filler, 0.27 g multi-walled carbon nanotubes, 39.6 g rubber matrix, 1.5987 g vulcanizing agent” is replaced by “120 g ZnO-based inorganic filler, 0.54 g multi-walled carbon nanotubes, 36 g rubber matrix, 1.5654 g vulcanizing agent”, and other conditions remain unchanged.
[0082] Example 5
[0083] The preparation process is basically the same as that in Example 1, except that “120 g ZnO-based inorganic filler, 0.27 g multi-walled carbon nanotubes, 39.6 g rubber matrix, 1.5987 g vulcanizing agent” is replaced by “120 g ZnO-based inorganic filler, 0.81 g multi-walled carbon nanotubes, 32.4 g rubber matrix, 1.5321 g vulcanizing agent”, and other conditions remain unchanged.
[0084] Example 6
[0085] The preparation process is basically the same as that of Example 1, except that "1.5987 g of vulcanizing agent" is replaced by "0.79935 g of vulcanizing agent", and other conditions remain unchanged.
[0086] Example 7
[0087] The preparation process is basically the same as that of Example 1, except that "1.5987 g of vulcanizing agent" is replaced by "1.279 g of vulcanizing agent", and other conditions remain unchanged.
[0088] Example 8
[0089] The preparation process is basically the same as that of Example 1, except that "39.6 g rubber matrix, 1.5987 g vulcanizing agent" is replaced by "31.35 g styrene-butadiene rubber matrix, 1.5162 g vulcanizing agent", and other conditions remain unchanged.
[0090] Example 9
[0091] The preparation process is basically the same as that in Example 1, except that "120 g ZnO-based inorganic filler and 39.6 g rubber matrix are divided into 10 equal parts and added sequentially" is replaced by "120 g ZnO-based inorganic filler and 39.6 g rubber matrix are added all at once", and other conditions remain unchanged.
[0092] Example 10
[0093] The preparation process is basically the same as that of Example 1, except that "gradually increase the speed to 60 r / min and stir for 15 min" is changed to "directly increase the speed from 5 r / min to 60 r / min".
[0094] Comparative Example 1
[0095] The preparation process is basically the same as that in Example 1, except that "120g ZnO-based inorganic filler, 0.27g multi-walled carbon nanotubes, 39.6g rubber matrix, 1.5987g vulcanizing agent" is replaced by "120g ZnO-based inorganic filler, 43.2g rubber matrix, 1.632g vulcanizing agent", and other conditions remain unchanged.
[0096] Comparative Example 2
[0097] The preparation process is basically the same as that in Example 1, except that "120g ZnO-based inorganic filler, 0.27g multi-walled carbon nanotubes, 39.6g rubber matrix, 1.5987g vulcanizing agent" is replaced by "135g ZnO-based inorganic filler, 39.6g rubber matrix, 1.746g vulcanizing agent", and other conditions remain unchanged.
[0098] Comparative Example 3
[0099] The preparation process is basically the same as that in Example 1, except that "120g ZnO-based inorganic filler, 0.27g multi-walled carbon nanotubes, 39.6g rubber matrix, 1.5987g vulcanizing agent" is replaced by "0.27g multi-walled carbon nanotubes, 68.4g rubber matrix, 0.6867g vulcanizing agent", and other conditions remain unchanged.
[0100] Test example
[0101] 1. SEM (scanning electron microscope): model SU8010, manufacturer Hitachi Co., Ltd., secondary electron resolution: 1.0nm (15kV), 1.6nm (1kV), acceleration voltage: ≥0.1~30kV, magnification: better than ×30~×200000, the equipment was used to characterize the microscopic morphology of ZnO-based inorganic fillers (10~20μm, varistor gradient 250V / mm) and composite films. The results are shown in Figures 1 to 15 .
[0102] 2. DC digital source meter: Model 2410C, manufacturer Keithley Instruments, power 20W, can provide and measure voltages from ±5μV (source) and ±1μV (measurement) to ±1100V, and currents from ±10pA to ±1A;
[0103] After the composite film was cross-sectioned by liquid nitrogen, the cross section was sprayed with gold for 30 seconds using a magnetron sputtering instrument to make the image clearer. The film samples used for the conductivity performance test were sprayed with gold for 90 seconds on both sides, and the mask was a 12mm diameter disc to ensure good contact with the electrode during the test.
[0104] A DC voltage ranging from 0 to 1100 V was applied to the composite membrane, 200 voltage points were applied, and the voltage increase rate was 5 V / s. The current at each voltage was tested. Three samples of each composite membrane were tested, and the average value was taken to plot the IU characteristic curve. In order to prevent the sample from being burned by excessive current, the current upper limit was set to 0.1 mA. The results are shown in Fig.16 .
[0105] 3. Hot Disk (thermal constant analyzer): model TPS2500S, manufacturer: Kegonas Instrument Trading (Shanghai) Co., Ltd., can measure the upper temperature limit of 3000℃, meets the transient plane heat source method in ISO 22007-2 standard, and has isotropic module, thin film test module, flat plate test module, low-density high insulation test module, and anisotropic test module.
[0106] The thermal conductivity of the composite film (thickness 200μm) at room temperature 25℃ was tested using a hot disk. The power applied by the hot disk was 2W and the test time was 20s. In order to reduce randomness, 5 samples of each composite film were measured and the average value was taken. The results are shown in Fig.17 .
[0107] according to Fig.16 It can be seen that the composite film of Example 1 exhibits excellent nonlinear conductivity characteristics. Among them, the IV curve of the composite film of Example 1 has good consistency, indicating that the dopant is evenly distributed in the base film. When the applied voltage is below 400V, the current of the sample does not exceed 1uA, maintaining good insulation performance. When the applied voltage is greater than 550V, the current of the sample increases rapidly and turns to the on state. This shows that the multi-walled carbon nanotubes do not destroy the nonlinear conductivity characteristics of the composite film.
[0108] according to Fig.17 It can be seen that the thermal conductivity of the composite film in Example 1 is 1.076W / mK. Comparing Comparative Example 1 and Comparative Example 2 with the composite film of the present invention, the results show that: compared with the ZnO / SiR composite film, the thermal conductivity of the composite film of the present invention is high, indicating that the doping of multi-walled carbon nanotubes can greatly improve the thermal properties of ZnO-based electric field adaptive materials. It can be concluded that doping multi-walled carbon nanotubes in ZnO-based composite materials can not only ensure electrical performance, but also greatly improve thermal conductivity (improvement of thermal performance), which is suitable for application scenarios with high comprehensive requirements for thermal performance.
[0109] The preferred specific embodiments and experimental verification of the present invention are described in detail above. It should be understood that ordinary technicians in this field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in this technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A highly thermally conductive adaptive composite film, characterized in that: It includes a rubber matrix film and a ZnO-based inorganic filler and a carbon nanotube doped in the rubber matrix film; The ZnO-based inorganic filler and the carbon nanotubes are independently doped inside and / or on the surface of the rubber matrix film; wherein the ZnO-based inorganic filler and the carbon nanotubes form an interconnected conductive network and a thermal conductive network in the rubber matrix film; The composite film comprises the following components in parts by mass: 20-30 parts of a rubber matrix, 60-80 parts of a ZnO-based inorganic filler, 0.1-10 parts of carbon nanotubes, and 0.5-1 parts of a vulcanizing agent; The particle size of the ZnO-based inorganic filler is 10-30 μm; The carbon nanotubes have an inner diameter of 2-5 nm, an outer diameter of less than 8 nm, and a length of 10-30 μm; The ZnO-based inorganic filler includes ZnO and a dopant doped in the ZnO; Wherein, the dopants include Bi2O3, MnO2, Co2O3, Cr2O3, Sb2O3, SiO2, and Al2O3.
2. The composite membrane according to claim 1, characterized in that The rubber matrix includes at least one of styrene-butadiene rubber and silicone rubber; and / or, The thickness of the composite film is 190-210 μm.
3. The composite membrane according to any one of claims 1 to 2, characterized in that: The thermal conductivity of the composite film is 1-1.5 W / mK.
4. A method for preparing a highly thermally conductive adaptive composite film according to any one of claims 1 to 3, characterized in that: The following steps are involved: The rubber matrix, the ZnO-based inorganic filler, the carbon nanotubes and the vulcanizing agent are mixed to obtain a composite material; The composite material is subjected to hot pressing treatment and cold pressing treatment in sequence to obtain a composite film.
5. The preparation method according to claim 4, characterized in that: The ZnO-based inorganic filler is prepared by a method comprising the following steps: ZnO and a dopant are mixed in proportion, and the mixture is subjected to ball milling and sintering to obtain the ZnO-based inorganic filler; and / or, The process of mixing the rubber matrix, the ZnO-based inorganic filler, the carbon nanotubes, and the vulcanizing agent includes: The rubber matrix, the ZnO-based inorganic filler and the carbon nanotubes equivalent to 10-20wt% of the total amount of the reaction raw materials are mixed under the first condition to obtain a first mixed system; the remaining rubber matrix, the carbon nanotubes and the ZnO-based inorganic filler are sequentially added to the first mixed system under the first condition to obtain a second mixed system; wherein the temperature under the first condition is 20-40°C and the rotation speed is 5-10r / min; After the second mixed system is subjected to a first speed-increasing treatment, a vulcanizing agent is added to the second mixed system under a second condition for reaction; wherein the rate of the first speed-increasing treatment is 5-10 r / min, the interval time is 20-30s, the temperature of the second condition is 20-40°C, and the rotation speed is 50-60 r / min.
6. The preparation method according to claim 4, characterized in that: The temperature of the hot pressing treatment is 170-180°C, the pressure is 10-15 MPa, and the time is 5-10 min; and / or, The temperature of cold pressing treatment is 20~25℃ and the time is 5~10min.
7. The preparation method according to claim 5, characterized in that: The ball milling temperature is 20-40°C and the time is 8-10 hours; and / or, The sintering temperature is 1200°C~1300°C and the time is 4~6h.
Citation Information
Patent Citations
Electric field self-adaptive composite material based on surface functionalization treatment and preparation method thereof
CN111875965A